Volunteering at the Workplace under Incomplete Information: Team Size Does Not Matter - Tobias Werner; Adrian Hillenbrand; Fabian Winter (ZBW - Leibniz Information Centre for Economics, 2020)
Volunteering is a widespread allocation mechanism at the workplace and emerges naturally in open-source software development, the generation of online knowledge platforms, and to some extent in "agile" work environments. Using a field experiment with 8 treatments and close to 2,800 workers on an online labor market, we study the effect of team size on volunteering at the workplace under incomplete information. In stark contrast to the theoretical predictions, we find no effect of team size on volunteering behavior. With the use of our control treatments, we can show that workers react to free-riding incentives provided by the volunteering setting in general, but do not react strategically to the team size. We show that the result is robust to several further factors.
Keywords: C93; C72; 330